KONSEP KESALAHAN RAKYAT DALAM KRITIK SOSIALIS TERHADAP DEMOKRASI LIBERAL ELEKTORAL - Zaky Diory Arvindo; Hasan Mud'is; Andi Nurlaela; Naan (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
This study aims to analyze the concept of the people’s error within socialist critiques of liberal electoral democracy by examining its philosophical foundations and ethical implications. The research employs a qualitative descriptive-analytical method based on conceptual and philosophical literature review. The formal object of the study is socialist political critique of liberal democracy, while the material object is the concept of the people’s error as articulated in critiques of electoral practices. The area of study lies within political philosophy, particularly debates on democracy, legitimacy, and emancipation in contemporary contexts. The analysis demonstrates that the notion of the people’s error functions as a normative construction emerging from structural failures of liberal electoral democracy rather than from inherent deficiencies of the people as political subjects. This narrative often shifts responsibility from institutional and economic structures to voters, generating ethical tensions between emancipatory aims and democratic equality. The study concludes that socialist critique must distinguish structural criticism from the delegitimization of popular sovereignty. It recommends further interdisciplinary research combining philosophical analysis with empirical investigation of democratic institutions and participatory alternatives.